Comprehensive care of elderly patients with hip fracture: the orthogeriatric model - Carlo Frondini; Maria L. Lunardelli (Italian Journal of Medicine, 2013)
Introduction: Hip fractures in the elderly are a major source of morbidity and mortality. Interdisciplinary hospital care models proposed for the treatment of these patients include consultant teams, integrated orthopedic-geriatric care, and comprehensive geriatric-led care settings. A prospective interventional cohort study was conducted in 4 public hospitals in the Emilia-Romagna Region of Italy to compare the outcomes of these different care models. This report presents the preliminary results obtained with an orthogeriatric model in one of these centers, a large teaching hospital in Bologna. Materials and methods: Beginning in February 2008, all patients older than 75 years admitted to the University of Bologna’s Sant’Orsola-Malpighi Hospital for hip fractures were cared for in an orthogeriatric unit. The unit consisted of 10 beds in the orthopedic ward that were managed by a geriatric specialist and a multidisciplinary team, which met daily and included an orthopedic surgeon, a physiatrist, a nurse case-manager, staff nurses, a physical therapist, and a social worker. The management protocol included a thorough geriatric work-up to identify comorbidities and risk factors, systematic assessment and prevention of pain and acute disorientation, early verticalization and moblization, postacute rehabilitation therapy, family support, and regular follow-up after discharge. Preliminary results were compared with those achieved in the same orthopedic ward prior to the creation of the Orthogeriatric Unit. Results: During 2008, 226 elderly patients (mean age 86.2 + 5.5 years), 73.4% of whom were women, were admitted to the Orthogeriatric Unit for hip fractures. The mean Charlson comorbidity index of this cohort was 3.0 + 1.8). Half the patients had Activity of Daily Living scores < 4, and cognitive impairment was common (mean score on Short Portable Mental Status Questionnaire: 5.9 + 3.2). Compared with figures obtained in the hospital’s orthopedic ward prior to 2008, in-hospital mortality dropped from 5.98% to 3.98%. The mean overall length of hospitalization was not significantly reduced, but the mean stay in the Orthogeriatric unit decreased by almost 2 days (to 10.46 days from 12.44 days in the traditional orthopedic unit). Discussion: Compared with traditional care models, the orthogeriatric model may allow better integration of the health-care resources available for the management of hip fractures in the elderly, and this improvement may have positive effects on the outcome of these cases.